P20-10. Differences in patterns of Gag-induced immunogenetic pressure occur between clades A and D chronic HIV-1 infection in a Ugandan population - Serwanga, J.; Ndembi, N.; Nanteza, B.; Mugaba, S.; Pimego, E.; Pala, P.; Auma, B.; Lyagoba, F.; Kaleebu, P. (Retrovirology, 2009)
We previously reported slow HIV-1 disease progression in this population to be associated with the inherent host HLA B allele-mediated ability to induce broader Gag T-cell responses and faster disease progression to be more associated with clade D than A. Since Gag escape mutations often reduce viral fitness leading to significant reduction in virus replication, in this study, we evaluated the immunogenetic characteristics of clades A and D-associated escape mutations that could be harnessed for vaccine design.
Keywords: Viral Fitness; Substitution A163G; Fast Disease Progression; Ugandan Population; Immunogenetic Characteristic